Understanding the urgency of Da'wah of Islam in the context of peace in the nuances of pluralism in Indonesia - Rahmah, St.; Aslamiah, Rabiatul (International research journal of management, IT and social sciences, 2023)
This article discussed the urgency of Da'wah in the context of peace and pluralism in Indonesia. The authors highlight the importance of Da'wah in promoting a peaceful and harmonious society in a diverse and pluralistic country like Indonesia. The article also analyzes the Muslim community's challenges in Indonesia, including the increasing misinterpretation of Islam and the threat of radicalism and extremism. The author also emphasizes the role of Da'wah in promoting tolerance and mutual understanding among different religions in Indonesia. We involve categorizing data into different themes or categories using software programs or manually, but the key is consistency in approach. While coding, we may see patterns and relationships between different themes. Next, we coded the data by starting to analyze it more deeply. This may involve looking for patterns and relationships between themes, comparing and contrasting responses, and identifying differences or outliers. Finally, we interpret the data to draw conclusions and insights. This may involve searching for underlying meanings or implications and considering how our findings relate to existing literature or theory. The article suggests that improving the understanding and skills of inclusive and responsive Da'wah can contribute to building a peaceful and tolerant society.